2022
DOI: 10.3389/fnins.2022.815282
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Development of Centrifugal Inputs to the Olfactory Bulb

Abstract: Processing in primary sensory areas is influenced by centrifugal inputs from higher brain areas, providing information about behavioral state, attention, or context. Activity in the olfactory bulb (OB), the first central processing stage of olfactory information, is dynamically modulated by direct projections from a variety of areas in adult mice. Despite the early onset of olfactory sensation compared to other senses, the development of centrifugal inputs to the OB remains largely unknown. Using retrograde tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…However, recent experimental evidence supports their contribution to the here‐described beta band coupling. Morphological assessment showed that centrifugal projections from the LEC and HP start to target the OB during the second postnatal week (Kostka & Bitzenhofer, 2022). They might account for the proportion of unit pairs with positive cross‐covariance lags during spontaneous activity that we described above.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent experimental evidence supports their contribution to the here‐described beta band coupling. Morphological assessment showed that centrifugal projections from the LEC and HP start to target the OB during the second postnatal week (Kostka & Bitzenhofer, 2022). They might account for the proportion of unit pairs with positive cross‐covariance lags during spontaneous activity that we described above.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, beta and gamma power in the OB was reduced following the silencing of MC terminals in the LEC (beta: med: −0.139, iqr: −0.256 to −0.074, P = 0.020; gamma: med: −0.075, iqr: −0.141 to −0.041, P = 0.027; n animals = 9; Wilcoxon's signed-rank test) (Fig. 8C and D) most likely as a result of reduced centrifugal feedback from the LEC and HP (Kostka & Bitzenhofer, 2022). Thus, the direct axonal projections from MCs to the LEC strongly contribute to the oscillatory entrainment of downstream limbic brain areas, such as the HP.…”
Section: Selective Inhibition Of MC Axonal Terminals In the Lec By Li...mentioning
confidence: 99%
“…Of note, beta and gamma power in OB was reduced following the silencing of MC terminals in LEC (RR: med: -0.002, iqr: -0.099 -0.086, p = 0.820; theta: med: -0.039, iqr: -0.127 -0.034, p = 0.426; beta: med: -0.139, iqr: -0.253 --0.074, p = 0.020; gamma: med: -0.062, iqr: -0.111 --0.020, p = 0.020; n=9; Wilcoxon signed-rank test) (Figs 7C and 7Di), most likely as result of reduced centrifugal feedback from LEC and HP [56].…”
Section: G and S10 Tablementioning
confidence: 97%
“… 59 , 60 , 61 In addition, the reduced OB responsiveness could result from abnormal feedback from downstream areas that target the OB via centrifugal projections and emerge during postnatal development. 62 , 63 …”
Section: Discussionmentioning
confidence: 99%